Pengaruh Obesitas Terhadap Kejadian Menarche Dini Pada Siswi SMPN 4 Watampone Kabupaten Wajo - Passe, rosita (ARTERI : Jurnal Ilmu Kesehatan, 2023)
The age of menstruation has shifted to a younger age if the first period begins before reaching 12 years old. Early menstruation in young girls can be caused by obesity, which is a result of excess fat intake. Consuming foods rich in fat can lead to increased fat storage in the body when not utilized as an energy source, subsequently elevating leptin hormone levels. This study aims to determine the impact of obesity on the occurrence of early menstruation among female students at SMP Negeri 4 Watampone, Kabupaten Bone.The utilized method is quantitative, employing a Cross-Sectional design. The population for this research consists of all female seventh-grade students at SMPN 4 Watampone, Kabupaten Bone, totaling 108 individuals. The sample size selected based on inclusion criteria was 47 respondents. The findings of this study indicate that out of 30 respondents with normal Body Mass Index (BMI), 27 respondents (90%) experienced menarche at the age of 12, and 3 respondents (17.6%) experienced menarche between the ages of 9 and 11. Additionally, among 17 respondents with excessive BMI, 3 respondents (10%) had menarche at the age of 12, while 14 respondents (82.4%) experienced menarche between the ages of 9 and 11.The analysis results reveal a significant correlation between obesity and the prevalence of early menstruation (ρ = 0.000, ρ < 0.05). Therefore, it is recommended that the school authorities enhance students' knowledge regarding the importance of nutrition and maintaining a healthy adolescent lifestyle. This information should be sourced from various reliable channels, including both teachers and healthcare professionals in the field of reproductive health..